Mercado brasileiro de biodiesel sob a ótica dos leilões públicos promovidos pela ANP: 2005 a 2014 - Amaral, Laila Cristina Gonçalves Silva (Universidade Federal do Tocantins, 2017)
Ten years ago, the actions of the National Program for Production and Use of Biodiesel (PNPB) inserted biodiesel in the Brazilian energy matrix. The sale of biodiesel in order to meet the stocks that the government needs to meet the requirement of mandatory blending percentage by law, is carried out through auctions and these are regulated by the National Petroleum, Natural Gas and Biofuels (ANP). Such legislation includes and gives privileges to participate in auctions to the holders of the Social Fuel Seal (SCS), which, in turn, is granted to companies taking over part of its raw materials from family farmers framed in the National Family Farming Strengthening Program (PRONAF). Thus, this study aims to identify and study the factors that influenced the evolution of Brazilian biodiesel market from the perspective of supply of the product in public auctions held by the ANP. First, we attempted to describe the evolution of biodiesel production in Brazil, detailing the major behavioral changes in the market and verify compliance with the main system functions. For this, general analyzes were made about offered and auctioned volumes, maximum and average prices, and discounts. The analysis of the market structure that best outlines the sector was made according to the degree of concentration of the participants of the auction company. For this we used the concentration ratio index (CR), the Herfindahl-Hirshman Index (HH) and the entropy index of Theil (TH). From the result of this, we sought to detect and quantify the factors affecting such rates. For this, we used the econometric practice with a multiple linear regression model. The data collected from the ANP site were analyzed using the statistical package Stata Corp LP, version 12.0, adopting the 95% confidence interval for analysis. The results showed that the biodiesel market in Brazil was concentrated initially, however, from the increased amount of participating companies, the mandatory blending percentage and ripening PNPB, the market was to decentralizing and making effective in moderately concentrated . Considering the studied literature, it appears that the biodiesel industry is characterized by oligopoly as market structure. More specifically, pure oligopoly.